Lílo ‘BBC News Yorùbá’ fún Ẹ̀kọ́ Yorùbá ní Amẹ́ríkà - Victor Temitope Alabi (Yoruba Studies Review)
I examined various means by which interviews made on ‘BBC News Yorùbá’ could be employed in Yorùbá language pedagogy in America. I then explored different topics that are generally treated in these interviews on ‘BBC News Yorùbá’ like politics, religion, sports, and business, and I classified these interviews into two: interviews made with an individual and interviews made with several people. Furthermore, I proposed a framework, which I named Yorùbá Dialectal Model (YDM). The framework submits that creators of authentic language resources in Yorùbá such as interviews (as I argued in this paper) and films (see Alabi, 2017) should consider the strict or the near strict use of the Yorùbá language in the communicative skills of writing and speaking. In a situation where new words that do not exist in Standard Yorùbá have to be borrowed; such words should be borrowed from dialects of Yorùbá rather than other languages. Finally, I analyzed an interview with Chief Ọbásanjọ́ to show the import of the framework and of interviews as authentic pedagogical resources in the Yorùbá language classroom across America.